Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Low carbon chemiluminescence detection of glucose by boosting of CCu bonding nanocomposites from epoxy resin waste debromination treatment - Yingying Qi; Man Zhao; Fu-Rong Xiu; Li Bai; Xiang Gao (Food Chemistry, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Electrochemical exfoliation of poly(triazine imide)-coated graphene oxide for the in-situ synthesis of composite proton exchange membranes with enriched phosphoric acid channels - Qingting Liu; Ying Zhou; Bei Wang; Zhiwei Ling; Xudong Fu; Rong Zhang; Shengfei Hu; Gang Xiao; Xiao Li; Feng Zhao; Jun Yang (Chemical Engineering Journal, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

GO-enhanced polyurethane phase change materials with triple dynamic bonds: Oxime-urethane, coordination and hydrogen bonds - Rong Huang; Fu Zhao; Yongsheng Li; Zhuoni Jiang; Fangfang He; Kai Zhang; Zhengguo Chen; Guansong He; Wenbin Yang (Chemical Engineering Journal, 2025)

One-pot strategy for multifunctional recyclable thermally conductive phase change composites toward efficient thermal management - Yunfang Li; Rong Zhang; Baokuan Zhou; Chenxi Liu; Xudong Fu; Hai Chen; Qingting Liu; Shengfei Hu (Chemical Engineering Journal, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Chemical constituents of the deep-sea-derived fungus Purpureocillium lilacinum XIA-18 and their chemotaxonomic significance - Bao-Fu Li; Yuan Wang; Zheng-Biao Zou; Rong Chao; Tai-Zong Wu; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)